Students’ Perception On The Use Of X Application In Vocabulary Building Of Tenth Grade Students At Sman 1 Glagah Banyuwangi - Nisrina Qurrotul ’Ain; wageyono; Wiwin Indiarti (LUNAR, 2025)
This research aims to describe students’ perceptions of using the X application as a medium for vocabulary building. Vocabulary mastery plays an important role in language learning, yet many students still face difficulties in expanding their vocabulary. The X application, which provides interactive vocabulary exercises and real-time feedback, is expected to help improve students’ vocabulary acquisition. The respondents were tenth-grade students at SMAN 1 Glagah Banyuwangi who used the X application. The researcher chose to limit the population to three tenth-grade classes. From these classes, the researcher identified 12 students who actively used the X application, selected based on their consistent engagement with the app to ensure relevant data. The sampling technique used was purposive sampling. This research employed a descriptive qualitative design. Data were collected through direct and WhatsApp interviews to explore students’ perceptions of using the X application for vocabulary building. The data were then analyzed descriptively to identify common themes in students’ responses. Based on the results of the data analysis, it can be concluded that the tenth-grade students at SMAN 1 Glagah have a positive perception of using the X application in vocabulary building. The X application helps students acquire new vocabulary, and they agree that it can be used as an alternative medium for vocabulary learning.